Opening Remarks During the Media Call on the Analytical Chapters of the June 2020 Global Economic Prospects Report - Malpass, David (World Bank, Washington, DC, 2020)
These opening remarks were delivered by World Bank Group President David Malpass during the media call on the analytical chapters of the June 2020 global economic prospects report on June 2, 2020. He covered about Bank's support activities, the debt service moratorium for the poorest countries, the progress on debt transparency and some of the next steps. He spoke about how the World Bank Group resources are being scaled up dramatically, providing strong net positive flows, especially to the poorest countries. He highlighted on IDA and IBRD working with countries to expand the coverage of social safety net programs, IFC providing finances to the private sector in developing countries over fifteen months, and MIGA helping to provide a more stable environment for investment by mitigating and managing risks arising from uncertainty. He described the debt moratorium that the World Bank and IMF championed, where the Debt service payments by all official bilateral creditors were suspended on May 1, adding to the potential resources for the poorest countries. He stated that an important part of this initiative is to help governments in debtor countries increase the transparency of their debt and investment practices and disclose the amounts and terms of their debt. He spoke about the Global Economic Prospects (GEP) report which finds a deep global recession, accompanied by a collapse in global trade, tourism and commodity prices and extraordinary market volatility. He said that beyond coping with the immediate crisis to limit the harm, policymakers can make a robust recovery more likely by maintaining private sector systems and infrastructure and allowing markets to allocate resources toward productive activities. He stated that most of the export restrictions that were announced earlier this year have not been implemented and global food prices have mostly remained stable. He highlighted on the important advances that are being made in digital connectivity in developing economies. He concluded by saying that the World Bank Group will continue to take broad, fast action in our response to the needs of people in developing countries.